1952
DOI: 10.1677/joe.0.0080179
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oestradiol on the Skeletal Muscle and Liver of the Rat

Abstract: The chemical composition of the liver and skeletal muscle in rats which had been treated with 1\m=.\0\g=m\g. oestradiol has been investigated. The water and electrolyte content, creatine and creatinine phosphorus fractions and total nucleoproteins were studied. The changes in the water content are reciprocal to those already described for the uterus. The creatine and creatinine content and the total nucleic acid do not change significantly. There is an increase of the acid-soluble phosphorus in the first phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1959
1959
1987
1987

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In humans, too, neither castration nor 237 238 PAMELA DANCE, SYBIL LLOYD AND MARY PICKFORD the post-menopausal state altered the response to oestradiol (Dignam et al 1956). The time after treatment when signs of water and electrolyte retention were maximal in dogs, namely 18-48 hr, is similar to the period in rats during which there is a marked increase in the water content of the tissues (Zuckermann, Palmer & Hanson, 1950;Cole, 1952). In rats the tissue water returned to normal after 48 hr.…”
Section: Discussionsupporting
confidence: 51%
“…In humans, too, neither castration nor 237 238 PAMELA DANCE, SYBIL LLOYD AND MARY PICKFORD the post-menopausal state altered the response to oestradiol (Dignam et al 1956). The time after treatment when signs of water and electrolyte retention were maximal in dogs, namely 18-48 hr, is similar to the period in rats during which there is a marked increase in the water content of the tissues (Zuckermann, Palmer & Hanson, 1950;Cole, 1952). In rats the tissue water returned to normal after 48 hr.…”
Section: Discussionsupporting
confidence: 51%
“…They do of course affect uterine size. In acute experiments on castrated female rats, Cole (1952) found that estradiol injections caused an increase in ECF volume in both muscle and liver, but a decrease in ICF volume. While there are no extant data on body composition, castrated girls tend to grow tall, and girls who have a late menarche tend to be taller than their postmenarchal age peers.…”
Section: Relationship Of Hormone Status To Body Compositionmentioning
confidence: 99%
“…In acute experiments on castrated female rats Cole (1952) found that estradiol produced an increase in ECF volume and a decrease in intracellular fluid (ICF) volume of both muscle and liver. Preedy and Aitken (1956) gave estradiol to human subjects.…”
Section: Estrogens Progesteronementioning
confidence: 99%
“…Calcium may thus have at least two actions in the rat uterus: the maintenance of (1) the idiomolar value and (2) the integrity of the cell membrane and of the 'sodium pump'. P. J. BENTLEY AND ALISON HOLLAND With regard to the first effect the rat uterus is known to have a larger and more labile idiomolar value than skeletal muscle (Cole, 1950(Cole, , 1951 and this is affected by oestradiol (Cole, 1950). Calcium is known to have a 'stabilizing' effect on proteins (Gurd & Wilcox, 1956), and as calcium is bound to intracellular structures forming bridges between anionic groups (Haurowitz, 1956) a loss of calcium may result in a break-down of organic molecules and increased idiomolar value.…”
Section: Discussionmentioning
confidence: 99%